Hollywood caught in two worlds? The impact of the Bechdel test on the international box office performance of cinematic films - Johann Valentowitsch (Marketing Letters, 2022)
The Bechdel test is increasingly used in academia as a quality indicator for the portrayal of women in films. Previous studies explored how passing the Bechdel test affects box office earnings. However, earlier considerations were all limited to the US market. Therefore, the impact of the Bechdel test on international box office receipts is still unclear. To fill this research gap, this study examines the box office effect for internationally released films at the country level. Using a sample of 515 randomly selected Hollywood films, it is shown that passing the test significantly improves international box office earnings. However, the results also show that the effect depends on the level of socioeconomic development in the respective countries. Cultural discount theory is used to explain the empirical findings.
Keywords: C21; F63; J16; L82; 380; Hollywood; Film industry; Box office performance; Bechdel test; Cultural discount